Health Care Professionals as Victims of Stalking: Characteristics of the Stalking Campaign, Consequences, and Motivation in Italy. Issue 17 (September 2017) - Acquadro Maran, Daniela; Varetto, Antonella; Zedda, Massimo; Franscini, Monica
Stalking is a phenomenon characterized by a set of repetitive behaviors, intrusive surveillance, control, communication, and search of contact with a victim who is afraid and/or worried and/or annoyed by such unwanted attention. Literature analysis shows that Health Care Professionals (HCPs) are at greater risk of being stalked than the general population. As described by Mullen, Pathé, Purcell, and Stuart, stalkers may have different motives: relational rejection, an infatuation, an inability to express their own emotions and recognize those of others, or a desire for revenge. The aim of this study was to explore stalkers' motivation as perceived by their victims, characteristics of stalking campaigns, and consequences. A copy of the Italian modified version of The Network for Surviving Stalking (NSS) Questionnaire on Stalking, the Beck Depression Inventory (BDI) and the State Trait Inventory (STAI) Y1-Y2 scales were distributed in six Italian state hospitals. Participants included 1, 842 HCPs, 256 (13.9%) of which had been victims. The majority of victims reported that stalkers were Rejected (96, 37.5%), Intimacy seekers (41, 16%), Incompetent suitors (60, 23.4%), and/or Resentful (43, 16.8%; χ 2 = 163.3, p = .001). Stalking campaigns were characterized by several behaviors, principally contact (by telephone calls, text message) and following. The stalking campaign caused in victims both physical and emotional consequences, the most frequent being weight changes, sleep disorders, weakness, apprehension, anger, and fear. The most used coping strategies were moving away and moving toward, the less used was moving inward. Intervention programs and preventive measures (both individual and organizational) for HCP victims and those who could be considered at risk are also discussed.